COMPARISON OF RSA AND ROT13 METHODS FOR TEXT FILE CONFIDENTIALITY - Rano, Rano Irawan; Hasugian, Abdul Halim; Sulindawaty (Bahasa Indonesia, 2024)
The word cryptography comes from the Greek:krupto (hidden or secret) and grafh (writing),meaning "secret writing". In the past,cryptography could be interpreted as the scienceand art of maintaining the security of data ormessages by encoding them in a form whosemeaning could no longer be understood. In itsdevelopment, cryptography is not only meant toencrypt data or messages, but also to maintain thesecurity of data or messages. The research carriedout by researchers is a type of research anddevelopment (R&D). The R&D research method isa research method used to produce certainproducts and test the effectiveness of theseproducts. R&D is a process or steps to develop anew product or improve an existing product,which can be accounted for. At this stage,encryption and decryption testing of eachalgorithm will be carried out on text data with anumber of characters varying between 10 to 100characters and the output What will be displayedis the encryption result in the form of a ciphertextfile and the running time. The implementation ofthe RSA cryptographic algorithm was successfuland the resulting system runs according to thealgorithm used and the encrypted plaintext can bereturned to its original form.